Evaluasi Implementasi Kebijakan Pengembangan Kawasan Industri - Syahrudiin, SYAHRUDDIN (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The research aims to evaluate the implementation of industrial area development policy in Karawang Regency, West Java. The research uses qualitative approach with in-depth interview with the related officials. The result of research shows that there has not been an effective communication among institutions, and there is a low availability of resources, i.e. human resources and infrastructures to arrange and implement the industrial area development policy. In addition, the industrial area development has not been the special focus of local government since industrial area developer is merely considered as an area development company instead of an investment partner, necessary to develop the industrial sector. The local government of Karawang Regency needs to improve its bureaucracy structure and bureaucracy culture in order to provide excellent public service and to use information technology advancement to attract investors.